Patient outcomes using the European label for dabigatran - Lip, Gregory Y. H.; Clemens, Andreas; Noack, Herbert; Ferreira, Jorge; Connolly, Stuart J.; Yusuf, Salim (Thrombosis and Haemostasis, 2014)
In the RE-LY trial dabigatran 150 mg twice daily (D150) showed significantly fewer strokes, and 110 mg (D110) significantly fewer major bleeding events (MBE) compared to well-controlled warfarin in patients with atrial fibrillation (AF). The European (EU) label currently recommends the use of D150 in AF patients who are aged < 80 years without an increased risk for bleeding (e.g. HAS-BLED score <3) and not on concomitant verapamil. In other patients, D110 is recommended. In this post-hoc analysis of the RE-LY dataset, we simulated how dabigatran (n=6,004) would compare to well-controlled warfarin (n=6,022) used according to the EU label. “EU label simulated dabigatran treatment” was associated with significant reductions in stroke and systemic embolism (hazard ratio [HR] 0.74; 95% confidence interval [CI] 0.60–0.91), haemorrhagic stroke (HR 0.22; 95%CI 0.11–0.44), death (HR 0.86; 95%CI 0.75–0.98), and vascular death (HR 0.80; 95%CI 0.68–0.95) compared to warfarin. Dabigatran was also associated with less major bleeding (HR 0.85; 95%CI 0.73–0.98), life-threatening bleeding (HR 0.72; 95%CI 0.58–0.91), intracranial haemorrhage (HR 0.28; 95%CI 0.17–0.45), and “any bleeds” (HR 0.86; 95%CI 0.81–0.92), but not gastrointestinal major bleeding (HR 1.23; 95%CI 0.96–1.59). The net clinical benefit was significantly better for dabigatran compared to warfarin. In conclusion, this post-hoc simulation of dabigatran usage based on RE-LY trial dataset indicates that “EU label simulated dabigatran treatment” may be associated with superior efficacy and safety compared to warfarin, and are in support of the EU label and the 2012 European Society of Cardiology AF guideline recommendations. Thus, adherence to European label/guideline use results in a clinically relevant benefit for dabigatran over warfarin, for both efficacy and safety.Note: The editorial process for this paper was fully handled by Prof Christian Weber, Editor in Chief.
Keywords: Atrial fibrillation; dabigatran; net clinical benefit; warfarin